TRANSFORMASI PEMBELAJARAN PANCASILA MELALUI MODEL PANORAMA DAN MEDIA EDUCATION PLAY: PENINGKATAN DISIPLIN DAN CRITICAL THINKING SISWA SD - Hidayati, Ernita Rizka; Pratiwi, Diani Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the issue of students' low levels of discipline and critical thinking skills. These challenges stem from monotonous and unvaried teaching methods, along with minimal student engagement during the learning process. Furthermore, students often become easily bored due to the use of unattractive learning models and media. This research is a form of Classroom Action Research (CAR) aimed at analyzing the improvement of students' critical thinking skills and discipline. The results show a significant increase in student discipline, with the percentage of students categorized as